The Role of Electronic Media in Spreading Islamic Da'wah: a Case Study at Kuala Lumpur - Aminah Bt Yusof (Universiti Sains Islam Malaysia, 2009)
The electronic media borderless world has a big influence towards people in spreading Islamic da'wah. The role of electronic media is strengthening the development of da'wah. Based on the above scenario, the study is constructed to know the society perception towards the electronic media as da'wah medium. Beside that, this study also establishes to identify the role and the effectiveness of electronic media in spreading Islamic da'wah. Surveys, questionnaire, and reviewing relevant documents are the tools employed for data gathering purpose. This research includes 40 respondents from Kuala Lumpur. The findings indicate that the electronic media play an important role in conveying Islamic da'wah and the usage of electronic media in Islamic da'wah is very effective. And finally, the study concludes that the use of media in spreading da'wah is well received by the society. So, the electronic media should increase and adds the Islamic programmers for the people in order to produce Muslim's quality.